Disaster risk reduction: Why do we need accurate disaster mortality data to strengthen policy and practice?. Issue 6 (9th October 2019) - Saulnier, Dell D.; Green, Helen K.; Ismail, Rohaida; Chhorvann, Chhea; Bin Mohamed, Norlen; Waite, Thomas D.; Murray, Virginia
Abstract : Purpose: The Sendai Framework for Disaster Risk Reduction 2015–2030 calls for a reduction in disaster mortality, yet measuring mortality remains a challenge due to varying definitions of disaster mortality, the quality, availability and diversity of data sources, generating mortality estimates, and how mortality data are interpreted. Design/methodology/approach: This paper uses five case studies to provide details around some of the complexities involved with measuring disaster mortality and to demonstrate the clear need for accurate disaster mortality data. Findings: The findings highlight the benefits of combining multiple data sources for accurate mortality estimates, access to interoperable and readily available global, national, regional and local data sets, and creating standardized definitions for direct and indirect mortality for easier attribution of causes of death. Originality/value: Countries should find a method of measuring mortality that works for them and their resources, and for the hazards they face. Combining accurate mortality data and estimates and leadership at all levels can inform policy and actions to reduce disaster mortality, and ultimately strengthen disaster risk reduction in countries for all citizens.